A PROBLEMS ARISING FROM TRANSFER PRICING - Nuredin, Mensur; Yakupova, Nazife (International Scientific Journal Vision, 2017)
We live in a time of fast technical-technological development and application of automatic data processing. The technological development of people offers a variety of opportunities for development and innovation. More precisely, we can say that we live in an era of information characterized by mass communication between people, states and companies. This development, especially with the emergence of e-commerce, has contributed to a large number of multinational companies that have the flexibility to market their businesses and activities anywhere in the world.Today, much of the global trade consists of international transfers of goods, services, capital and intangible assets (intellectual property) that take place within a multinational company group. Just when these intra-company transactions or transfers take place, occurs the phenomenon of transfer pricing.The “transfer pricing” in the literature is presented as a technique for the most favorable distribution of revenues and expenditures between subsidiaries, branches and joint ventures within a group of interconnected entities. The subsidiaries and branches of multinationals have the ability to manipulate their intra-company transaction accounts. That is, they can perform these transactions for a higher or lower price than the determined market price. Therefore, this study analyzes the basic problems that arise due to transfer pricing and after the problem is identified, the proposed and used solutions will be considered.